2023
DOI: 10.1111/pbi.14181
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐based genome editing of 14 lipid metabolic genes reveals a sporopollenin metabolon ZmPKSB‐ZmTKPR1‐1/‐2 required for pollen exine formation in maize

Xueli An,
Shaowei Zhang,
Yilin Jiang
et al.

Abstract: SummaryLipid biosynthesis and transport are essential for plant male reproduction. Compared with Arabidopsis and rice, relatively fewer maize lipid metabolic genic male‐sterility (GMS) genes have been identified, and the sporopollenin metabolon in maize anther remains unknown. Here, we identified two maize GMS genes, ZmTKPR1‐1 and ZmTKPR1‐2, by CRISPR/Cas9 mutagenesis of 14 lipid metabolic genes with anther stage‐specific expression patterns. Among them, tkpr1‐1/‐2 double mutants displayed complete male steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…Homologous proteins are generally similar functionally, reaffirming the preserved function of GhTKPR1_8 in pollen wall formation and shedding light on its potential additional roles in anther dehiscence (Peng et al, 2023). Generally, TKPR1 s show congruous expression patterns and localization at the tetrad stage in other species, such as Arabidopsis , rice, and maize (Grienenberger et al, 2010; Xu et al, 2019; An et al, 2024). We demonstrated that GhTKPR1_8 and GhTKPR1_17 showed typical expression patterns in the anthers of 3–6 mm buds (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homologous proteins are generally similar functionally, reaffirming the preserved function of GhTKPR1_8 in pollen wall formation and shedding light on its potential additional roles in anther dehiscence (Peng et al, 2023). Generally, TKPR1 s show congruous expression patterns and localization at the tetrad stage in other species, such as Arabidopsis , rice, and maize (Grienenberger et al, 2010; Xu et al, 2019; An et al, 2024). We demonstrated that GhTKPR1_8 and GhTKPR1_17 showed typical expression patterns in the anthers of 3–6 mm buds (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…OsTKPR1‐ loss‐of‐function mutations in rice degraded the tapetum, suppressed the levels of anther cuticular lipids, and disrupted the ubisch body and exine formation, ultimately leading to total male sterility (Xu et al, 2019). A maize double mutant, zmtkpr1 _ 1 / zmtkpr1 _ 2 , exhibited absolute male sterility, accompanied by delayed tapetal degradation, a defective exine, and abnormal anther cuticles (An et al, 2024). The tkpr1 mutant of Cryptomeria japonica displayed a thinner pollen wall compared to the wild type, reduced pollen grain count, and the production of non‐viable pollen (Kakui et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq data for ZmALDHs in 14 tissues were obtained from MaizeGDB qTeller (). RNA-seq data of three maize inbred lines W23, B73, and Oh43 developing anthers were obtained from previously published articles. Expression data are visualized in a heat map by TBtools.…”
Section: Methodsmentioning
confidence: 99%
“…It can accelerate the efficiency of breeding by performing precise and predictable modifications of the target genes. For example, CRISPR/Cas9-based gene editing was used to simultaneously mutate multiple homologous genes required for pollen development and male fertility in maize, which definitely contributes to male-sterility line-assisted maize hybrid breeding. CRISPR/Cas9 was used to make weak promoter alleles of CLV3/ESR-RELATED ( CLE ) genes and a null allele of a newly identified partially redundant compensating CLE gene to increase multiple maize grain-yield-related traits . Meanwhile, CRISPR/Cas9 is often used to make double knockout mutants.…”
Section: Modern Breeding Strategies In Maize Improvementmentioning
confidence: 99%